Structural optimization of porous CPC scaffolds and the effect of eliminating the outer wall on mechanical properties for bone regeneration - Pilekic, Christian; Lienhard, Jörg; Shetty, Sunil; Pichotka, Martin Peter; Schmal, Hagen; Seidenstuecker, Michael (Frontiers in Mechanical Engineering, 2026)
Additive manufacturing was utilized to fabricate rotationally symmetrical scaffolds from CPC, which exhibit sufficient mechanical stability to function as bone replacement and possess sufficient accessible surface area for subsequent release of active ingredients. An existing geometry was further developed for this purpose. The experimental protocol entailed an initial phase of solidification in an atmosphere saturated with water, followed by a post-solidification phase in Phosphate Buffered Saline (PBS). Furthermore, a pause was inserted after every five layers during three-dimensional plotting, and the green bodies were sprayed with water. The study also investigated the influence of water content on mechanical strength. A comprehensive examination of the test specimens was conducted under macroscopic, microscopic, and mechanical scrutiny. The scaffolds demonstrated an adequate capacity to withstand a load of 2,000 N (N). Subsequent to consolidation in Phosphate Buffered Saline (PBS), there was no observed increase in the maximum tolerated force. At this breaking load, the majority of test series exhibited an average deformation of 5%. The resultant stiffness was measured at 1,100 MPa. Consequently, the samples exhibited a strength level that was lower than that of spongy bone. The investigation revealed that the novel geometry, featuring an open outer ring, exhibited adequate mechanical stability while concomitantly augmenting the surface area accessible from the exterior for subsequent drug release. The advent of mass production with the new geometry is now a possibility.